2022
DOI: 10.3390/agronomy12071541
|View full text |Cite
|
Sign up to set email alerts
|

Performance of AquaCrop Model for Maize Growth Simulation under Different Soil Conditioners in Shandong Coastal Area, China

Abstract: Evaluating the performance of AquaCrop models under the drip irrigation of maize with soil conditioners is of great significance for improving coastal saline–alkali land crop management strategies. This study aimed to evaluate the performance of an AquaCrop model for maize growth simulation under different soil conditions (humic acid (HA) and sodium carboxymethyl cellulose (CMC)) and dosages and different levels of irrigation in the Shandong coastal saline–alkali area, China, and to optimize the amount of irri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
(24 reference statements)
1
3
0
Order By: Relevance
“…However, it was noted that the model adequately estimated the water dynamic in the soil, satisfactorily representing the soil moisture behavior, especially during the water deficit phases. Other studies have shown results similar to the ones found in the present study (HUANG et al, 2022;AHMADI et al, 2022;SHAN et al, 2022).…”
Section: Resultssupporting
confidence: 93%
“…However, it was noted that the model adequately estimated the water dynamic in the soil, satisfactorily representing the soil moisture behavior, especially during the water deficit phases. Other studies have shown results similar to the ones found in the present study (HUANG et al, 2022;AHMADI et al, 2022;SHAN et al, 2022).…”
Section: Resultssupporting
confidence: 93%
“…The final calibration results of parameters in AquaCrop-OSPy are shown in Table 5. The relevant parameters are essentially consistent with the values of Shan et al (2022) for the AquaCrop constructed for corn in this experimental area [34]. In the "Remarks" column, "Calibrated" indicates that the values were calibrated using the data measured in 2019-2021, "Measured" indicates measured data, and "Recommended" indicates that the value was recommended in the AquaCrop manual.…”
Section: Calibration and Validation Of The Aquacrop-ospy Modelsupporting
confidence: 59%
“…The results show that after calibration, the model parameters could accurately simulate the CC (R 2 ≥ 0.87, NRMSE ≤ 19%) and BIO (R 2 ≥ 0.96, NRMSE ≤ 11.6%) of corn, and the simulation effect under the irrigation scenario was better than that under rain-fed conditions, which may be related to the uneven distribution of rainfall in the region leading to water stress in rain-fed corn. The simulation accuracy of AquaCrop under water stress decreased, which was confirmed by Sandhu and Irmak et al [3,34].…”
Section: Discussionmentioning
confidence: 57%
“…Notably, it has been successfully coupled with remote sensing data, specifically green fractional vegetation cover, to estimate maize growth and total aboveground dry biomass in Belgium (Mohamed Sallah et al, 2019). Additionally, its efficacy has been demonstrated in investigating diverse irrigation treatments in Semi-Arid Tropical areas of India (Umesh et al, 2022), as well as exploring varied soil conditions' impact on maize growth (Shan et al, 2022).…”
Section: Mechanistic-deterministic Models In Precision Agriculture Ap...mentioning
confidence: 99%